Womanhood at the crossroads the lumad perspective. [article]. - Abrenica, Alexa P.
The concept of womanhood before and after menopause was explored among Mansaka women using a focus group discussion. The Mansaka is an indigenous tribe in southern Mindanao. The results show that for the Mansaka women, womanhood is intimately interwoven into the relationship and service to husband and children before menopause and service to husband, children and grandchildren after menopause. menopause is a non-event in view of the women acquisecent acceptance of aging as part of the cycle of life.